Hubungan Public Relation Skill Dan Kompetensi Petugas Pendaftaran Pasien Dalam Penanganan Complain di Rumah Sakit X - Nisa, Syayidatun; Mamesah, Marline Merke; Wijaya, Hermanto; Kurniawan, Afif; Putri, Linta Meyla (Journal of Health Management Research; Vol 3 No 1 (2024): Journal of Health Management ResearchDO - 10.37036/jhmr.v3i1.469, 2024)
Background: The health service has a public relations division which can be considered important in carrying out its duties. One of the tasks of public relations itself is to handle patient komplaints. Aims: know the relationship between public relations skills and the competency of patient registration officers in handling komplaints. Methods: This research uses a quantitative descriptive method with an approach of distributing questionnaires to officers with 6 respondents. Results: the results obtained on the independent and dependent variables, namely the relationship between competence and patient handling in the moderate category, officer communication with komplaint handling in the low category and job description with komplaint handling in the moderate category. Conclusion: The conclusions obtained are the competence of officers in handling related komplaints, the communication of officers in handling related komplaints and the job description of officers in handling related komplaints.